Pelakasanaan Kurikulum Dalam Meningkatkan Penetapan Tujuan Pendidikan di Madrasah - Al Kautsary, Muhammad Iqbal (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This study examines the implementation of the curriculum at Madrasah Aliyah Negeri 3 Karawang and its impact on achieving educational goals, encompassing the spiritual, academic, and social aspects of students. Against the backdrop of the need to preserve Islamic values amidst the dynamics of changing times, this research aims to analyze the extent to which the implemented curriculum can support the madrasah’s vision and mission in shaping students with noble character. The methodology used is descriptive qualitative, with data collection through documentation and observation. The findings indicate that the curriculum implementation at MAN 3 Karawang has successfully integrated Islamic values into the learning process and student activities, as evidenced by the improvement in their spiritual and moral competencies. The implications of these findings highlight the need for continuous curriculum adjustments to maintain relevance with modern educational needs without neglecting the foundational Islamic values. This research contributes to the development of educational strategies in madrasahs to face contemporary challenges and enhance the quality of Islamic education.